2015
DOI: 10.1186/1471-2261-15-5
|View full text |Cite
|
Sign up to set email alerts
|

Nemaline myopathy and heart failure: role of ivabradine; a case report

Abstract: BackgroundNemaline myopathy (NM) is a rare congenital myopathy characterized by muscle weakness, hypotonia and the presence in muscle fibers of inclusions known as nemaline bodies and a wide spectrum of clinical phenotypes, ranging from severe forms with neonatal onset to asymptomatic forms. The adult-onset form is heterogeneous in terms of clinical presentation and disease progression. Cardiac involvement occurs in the minority of cases and little is known about medical management in this subgroup of NM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The same study also reported that there was no difference in the survival of the participants aged over 65 years compared to younger participants (eligible patients up to age 80 years were treated in the study) [50], although a prior study of another group had suggested that patients 65 years of age or older should not be considered for the treatment [51]. In SLONM-MGUS, as described early, cardiac muscle involvement is possible, and elderly patients can also be encountered [8,19,20,22]. In such cases, indication of HDM-SCT should be considered more carefully.…”
Section: Treatmentmentioning
confidence: 96%
See 4 more Smart Citations
“…The same study also reported that there was no difference in the survival of the participants aged over 65 years compared to younger participants (eligible patients up to age 80 years were treated in the study) [50], although a prior study of another group had suggested that patients 65 years of age or older should not be considered for the treatment [51]. In SLONM-MGUS, as described early, cardiac muscle involvement is possible, and elderly patients can also be encountered [8,19,20,22]. In such cases, indication of HDM-SCT should be considered more carefully.…”
Section: Treatmentmentioning
confidence: 96%
“…The left ventricular ejection fraction (LVEF) was reduced to 30%, but it recovered to 60% after chemotherapy of bortezomib, cyclophosphamide and dexamethasone, together with selective beta-blockers. In another report, a 37-year-old patient was pointed out to have left ventricular systolic dysfunction due to diffuse hypokinesia within 2 years after the onset of muscle weakness [20]. Subsequently, severe congestive heart failure with 20% of LVEF appeared, and three cardiac arrests due to ventricular tachycardia and fibrillation occurred, requiring intensive care and an implantable cardioverter defibrillator.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations